Carta Geografica del Norte y Nor-Oriente Peruano - W. de Greenwich (My University, 1932)
The present study shows the study of the Geographic Chart of Northern and Northeastern Peru.

El presente muestra el estudio de la Carta Geografica del Norte y Nor-Oriente Peruano.
Geographic Chart of Northern and Northeastern Peru
Keywords: Iquitos (Peru)--maps; Peru--cartographic materials; Peru--maps